2014
DOI: 10.4149/neo_2014_043
|View full text |Cite
|
Sign up to set email alerts
|

The biological markers and results of treatment in male breast cancer patients. The Cracow experience.

Abstract: Male breast cancer is a rare form of carcinoma with an incidence rate of approximately 0.5-1% compared with cases of breast carcinoma as a whole. Male breast cancer reacts effectively to endocrine therapy because of a high frequency of hormone receptor expression.The aim of the present study was the assessment of correlations between stage, grade, expression of steroid receptors, basal/mesenchymal markers and proliferation index, as well as analysis of the impact of the above-mentioned parameters on overall (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(122 reference statements)
0
3
0
Order By: Relevance
“… 17 In the present study, tumour stage, grade and ER status were independent prognostic factors for OS. 18 Therefore, to further understand the association between adjuvant chemotherapy and the survival of stage I–III male breast cancer patients, we stratified the patients by tumour grade, stage, receptors status, tumour size and LN status. The data of HER2 status were available only after 2010 due to limitations in the SEER database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 In the present study, tumour stage, grade and ER status were independent prognostic factors for OS. 18 Therefore, to further understand the association between adjuvant chemotherapy and the survival of stage I–III male breast cancer patients, we stratified the patients by tumour grade, stage, receptors status, tumour size and LN status. The data of HER2 status were available only after 2010 due to limitations in the SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…10 Several large clinical trials have shown that some women with breast tumour >1 cm may avoid adjuvant chemotherapy without reducing the overall survival rate. 11 For example, the TAILORx trial 12,13 was a prospective and randomized trial for women with hormone receptor-positive, human epidermal growth factor receptor 2-negative, stage T1-2, lymph node-negative and recurrence score (RS) of 11-25 breast cancers (HR+, HER2-, T1-2, N0, M0, RS [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], in which the patients received adjuvant endocrine therapy alone or adjuvant chemotherapy followed by endocrine therapy. The two groups had similar treatment efficacy and no significant differences in disease-free survival (DFS) or overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…For both sexes, prognostication and treatment decision making is dependent upon the expression pro les of the nuclear hormone receptors ERα and PR, currently determined by immunohistochemistry. High expression of ERα and PR are both predictors of improved outcome in MBC, associated with improved overall and disease-free survival, older age of diagnosis, low mitotic index, and lower pathological stage [6][7][8][9][10][11][12][13] The expression of these receptors is notably different between MBC and FBC. Contrary to females, BC in males is almost universally ERα positive (95% in MBC vs. 75% in FBC).…”
Section: Introductionmentioning
confidence: 99%